2007
DOI: 10.1007/s11269-007-9156-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Sediment Transport in Meandering Channels

Abstract: Sediment transport in a meandering channel is measured in a laboratory flume. The measurements are evaluated and compared with previous studies. The values of the calculated sediment transport rates using previous formulas are generally overestimated. Under these circumstances, in this research, it is noticed that the sediment transport rates as measured in the laboratory, and sediment transport capacities computed with the Einstein's approach, behave in a quite similar way, seemingly closely related to the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The channel curvature therefore affects the routing of fine and coarse grain size fractions of the bed load, which are disproportionately transported in different regions of the channel: finer particles are transported in great quantity in the inner portions of bends and coarser grains are disproportionately moved through the outer regions (Parker and Andrews, 1985;Ikeda, 1989;Bridge, 1992), as documented in field studies for both sand-bed (Bridge and Jarvis, 1976;Dietrich andSmith, 1983, 1984) and gravel-bed (Clayton and Pitlick, 2007) rivers, as well as experimental channels (Nelson et al, 2010), though other experimental studies suggest that grain size sorting effects are difficult to scale appropriately in flume studies of meandering rivers (Yilmaz, 2008). Results from these and other studies (e.g., Whiting and Dietrich, 1991;Lisle et al, 2000) suggest that small, limited areas of the bed may convey large portions of the bed load in curved reaches.…”
Section: Introductionmentioning
confidence: 99%
“…The channel curvature therefore affects the routing of fine and coarse grain size fractions of the bed load, which are disproportionately transported in different regions of the channel: finer particles are transported in great quantity in the inner portions of bends and coarser grains are disproportionately moved through the outer regions (Parker and Andrews, 1985;Ikeda, 1989;Bridge, 1992), as documented in field studies for both sand-bed (Bridge and Jarvis, 1976;Dietrich andSmith, 1983, 1984) and gravel-bed (Clayton and Pitlick, 2007) rivers, as well as experimental channels (Nelson et al, 2010), though other experimental studies suggest that grain size sorting effects are difficult to scale appropriately in flume studies of meandering rivers (Yilmaz, 2008). Results from these and other studies (e.g., Whiting and Dietrich, 1991;Lisle et al, 2000) suggest that small, limited areas of the bed may convey large portions of the bed load in curved reaches.…”
Section: Introductionmentioning
confidence: 99%
“…According to model hypotheses, and provided that overbank flows are not required for neck cutoff (Gay et al., 1998; Hooke, 1995), the two runs were carried out at constant Q = 0.00025 m 3 /s, which was a flow rate value smaller than the bankfull limit. The two runs differed in terms of critical meander centerline curvature radius r 0 and, therefore, in terms of r 0 /B ratio, which is widely recognized as a morphological factor crucially affecting lateral migration rate (Hickin & Nanson, 1984; Richard et al., 2005) and meander cutting (Crosato, 2009; Yilmaz, 2008).…”
Section: Laboratory Experiments and Theory Validationmentioning
confidence: 99%
“…One of such studies was study of Yilmaz (2008), who performed experimental study of sediment transport in meandering channels measured in a laboratory ume and those measurements were evaluated and compared with previous model studies. They found that the values of the calculated sediment transport rates are generally overestimated.…”
Section: Introductionmentioning
confidence: 99%